Life threatening bleeding under adequate oral anticoagulation - Aegerter, Ch.; Fontana, St.; Fux, Ch.; Biasiutti, F. Demarmels (Hämostaseologie, 2003)
We report on two men with severe and recurrent bleeding episodes under well performed phenprocoumon therapy. Both patients showed an INR value within the therapeutic/subtherapeutic range with an inappropriately prolonged activated partial thromboplastin time (aPTT). The vitamin K-dependent coagulation factors were in the expected range, except for factor IX, which was as low as in moderate haemophilia B. After substitution of vitamin K, factor IX and the aPTT recovered completely in one case. In the other case factor IX was not measured but aPTT normalized. Diagnosis of an increased sensitivity of factor IX to phenprocoumon was assumed and proven in both cases by the demonstration of a missense mutation at ALA-10 in the factor IX propeptide.
Keywords: Oral anticoagulation; bleeding; factor IX propeptide mutation